Analysis of genetic variations of protein tyrosine kinase fyn and their association with alcohol dependence in two independent cohorts - Schumann, Gunter; Rujescu, Dan; Kissling, Christian; Soyka, Michael; Dahmen, Norbert; Preuss, Ullrich W.; Wiemann, Stefan; Depner, Martin; Wellek, Stefan; Lascorz Puértolas, Jesús; Bondy, Brigitta; Giegling, Ina; et al. (Biological psychiatry, 2003)
Abstract Background Decreased sensitivity to and increased tolerance for the effects of alcohol is a phenotype, which was shown to be associated with an increased risk for alcoholism in humans and was observed in protein tyrosine kinase (PTK) fyn knockout mice. Methods We performed an association study of genetic variations of PTK fyn in 430 alcohol-dependent patients and 365 unrelated control subjects from two independent samples. Results In a combined analysis, we found an association of alcohol dependence with the single nucleotide polymorphism (SNP) T137346C in the 5′ untranslated region (UTR) of the gene. A relevant association could be excluded for the remaining two informative SNPs. Selection by phenotype showed that a high number of withdrawal symptoms, high amount of alcohol intake, and high maximum number of drinks compared with unrelated control subjects was associated with the SNP in the 5′-UTR region but not with the remaining SNPs. Conclusions Our results indicate a possible association of alcohol dependence with a genotype of the SNP T137346C of the PTK fyn, with C being the risk allele.